Effectiveness of the Implementation of the Quizizz Application in Mathematics Subjects - Fitriani; Haripuddin; Zulhajji (Journal of Educational Studies in Science, Technology, Engineering, Arts and Humanities, 2026)
Technological developments in the field of science are increasingly driving efforts to renew the use of technology in the learning process to make it more effective. This requires educators to be able to use technology and media to support the learning process. Technological developments, especially in the era of the 4.0 industrial revolution, are expected to provide a solution. Entering the 21st century, the world has begun to enter the era of the 4.0 industrial revolution. The current era of the 4.0 industrial revolution prioritizes technological development and advancement in its application. This study aims to describe student learning outcomes and responses. This study used a quasi-experimental method with active students majoring in Mathematics at SMAN 15 Makassar who were studying Mathematics as subjects. The control class and the experimental class each consisted of 34 students. Data collection techniques included pre-tests, post-tests, and questionnaires. Data analysis techniques included descriptive statistics. The results showed that the average pretest score for the experimental class was 62.24 and the average pretest score for the control class was 66.26. It can be seen that the pretest scores for the experimental class were lower than those for the control class. Meanwhile, the average posttest score for the experimental class was 82.79 and the average posttest score for the control class was 79.29. It can be seen that the posttest score for the experimental class was higher than that of the control class, and the students' responses were in the very good category, with an average score of 32.91.